SPIRITUAL WELLBEING OF YOUNG FEMALE ADULTS: A Psychologist’s Perspective - S, Elizabeth C (Journal of Dharma, 2005)
The concept of wellness or wellbeing has been evolving in various disciplines, and attempts have been made to develop a description of an individual’s total wellbeing. Every human person yearns within oneself to lead a good life and even desires for a life that is peaceful, happy and meaningful. Several authors and researchers have attempted definitions of wellbeing. According to Clinebell, “you are whole or have wellbeing to the degree that the centre of your life is integrated and energized by love and healthy spirituality.”1 For him the whole person’s wellbeing includes: Loving oneself by developing one’s unique gifts of body, mind and spirit as fully as one can, at each stage of one’s life, loving other people by encouraging them to develop their unique gifts; loving one’s work, and one’s play, i.e., one’s vocation and avocation; loving the planet Earth, our mother, and her wonderful network of living things, caring for her and helping her, healing her wounds, and loving the Divine Spirit, the source of all healing and wholeness.